2014
DOI: 10.1002/ab.21528
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous alcohol use and intimate partner aggression among dating couples: The role of impulse control difficulties

Abstract: To date, research identifying moderators of the alcohol-intimate partner aggression (IPA) relationship has focused almost exclusively on male-perpetrated aggression, without accounting for the dyadic processes of IPA. The current study examined hazardous alcohol use and impulse control difficulties as predictors of IPA among a sample of 73 heterosexual dating couples. Both actor and partner effects of these risk factors on physical and psychological aggression were examined. Results indicated that impulse cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 85 publications
8
47
1
1
Order By: Relevance
“…21,2633 These findings are consistent with theoretic models that propose that substance use will more likely lead to partner violence among individuals with greater propensity for aggression. 21,25 The basic reasoning underlying these models posits that individuals vary in their aggression threshold, which is the point at which the strength of aggressive motivation exceeds the strength of aggressive inhibitions; when the threshold is exceeded, violent behavior results.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…21,2633 These findings are consistent with theoretic models that propose that substance use will more likely lead to partner violence among individuals with greater propensity for aggression. 21,25 The basic reasoning underlying these models posits that individuals vary in their aggression threshold, which is the point at which the strength of aggressive motivation exceeds the strength of aggressive inhibitions; when the threshold is exceeded, violent behavior results.…”
Section: Introductionsupporting
confidence: 83%
“…4,5,10,11 This notion is consistent with numerous theoretic “interaction” models that suggest the effects of substance use on PDVP will vary depending on characteristics of the individual and their social context. 2125 Some research with adults supports this proposition 21,2633 ; however, few studies have examined moderators of the linkage between substance use and adolescent PDVP. A better understanding of the contextual factors that condition associations between substance use and PDVP could inform primary prevention efforts that go beyond focusing exclusively on individual risk factors to changing the social contexts that influence risk for substance-related PDVP.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that major predictors of IPV perpetration, such as illegal substance use (apart from sedative use), were identical between genders. Like in previous studies 24,34 our findings suggest that the profile of IPV goes beyond gender differences, being more related to exposure to substance use, 35,36 especially cocaine. 37 The coexistence of victimization and aggression is an important issue that has received attention over the last decades.…”
Section: Discussionmentioning
confidence: 38%
“…Because we analyzed couples, we used a series of actor-partner interdependence models (APIMs; Kenny, Kashy, & Cook, 2006). APIMs are a standard way to analyze dyadic data (Brunell et al, 2010;Brunell, Pilkington, & Webster, 2007;Brunell & Webster, 2013;Smith et al, 2014;Webster, Laurenceau, et al, 2015) and are used in aggression research (Crane, Testa, Derrick, & Leonard, 2014;Dickson et al, 2015;Parrott et al, 2012;Watkins, Maldonado, & DiLillo, 2014). APIMs estimate actor and partner effects simultaneously.…”
Section: Aggression and The Dark Triadmentioning
confidence: 99%